The Effectiveness of Problem-Based Learning Model in Developing Critical Thinking Skills on the “Youth Pledge” Topic Within the Framework of “Bhinneka Tunggal Ika” - Nurul Azizah; Elly Hasan Sadeli; Ratna Kartika Wati (UM Purwokerto Press, 2023)
This research aims to determine the effectiveness of the Problem-Based Learning (PBL) model in developing critical thinking skills on the